O papel da edição na construção do gosto literário - Garcez, Isabel (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
The argument that will sustain this part of the course work that only published literary works (made public) have social existence principle. So, try to understand the meaning of the editing process, the act of turning a novel into a work edict, that is, a work available to be received. This process entails undeniable social, cultural and ideological implications, but we will address only the topic of the construction of literary taste and responsibility held by respective editors and publishers, as cultural mediators that enable the existence of a range of works that participate decisively in the construction of prevailing literary taste. The figure editor studied in this work belongs solely to the private business sector and therefore does not contemplate public bodies that perform the same function.
Keywords: Edition; Cultural mediation; Literary taste